Overview of Logistics Equilibrium Distribution Networks System: An Urban Perspective - Wang, Wei; Rahman, Md. Arafatur; Ali, Md Jahan; Bhuiyan, Md Zakirul Alam; Liu, Yao; Hai, Tao (Springer, 2018)
Logistics Equilibrium Distribution Networks System is a design scheme which provides the logistics distribution mechanism effective and efficient in terms of several layering aspects: business layout layer, supervision and evaluation layer and planning control layer. It enhances the monitoring function of the information platforms and the design scheme of the planning by controlling the distribution layer moving forward to control the whole system macroscopically to ensure the effective operation. To develop such network toward Urban perspective is a challenging task because of the various distribution layouts control. To address such an issue, this paper proposes a hierarchical ranking urban logistics equilibrium system, which incorporates the functional structure, the distribution system structure, and the operation mechanism in order to realize the high-end and integration of distribution system. The outcome of this research will assist to design an urban distribution system which can improve the distribution efficiency of urban logistics, save transportation costs, reduce carbon emissions, protect the urban environment, and promote the development of urban economy.